The power of moral words: Loaded language generates framing effects in the extreme dictator game - Capraro, Valerio; Vanzo, Andrea (Judgment and decision making, 2019)
Understanding whether preferences are sensitive to the frame has been a major topic of debate in the last decades. For example, several works have explored whether the dictator game in the give frame gives rise to a different rate of pro-sociality than the same game in the take frame, leading to mixed results. Here we contribute to this debate with two experiments. In Study 1 (N=567) we implement an extreme dictator game in which the dictator either gets $0.50 and the recipient gets nothing, or the opposite (i.e., the recipient gets $0.50 and the dictator gets nothing). We experimentally manipulate the words describing the available actions using six terms, from very negative (e.g., stealing) to very positive (e.g., donating) connotations. We find that the rate of pro-sociality is affected by the words used to describe the available actions. In Study 2 (N=221) we ask brand new participants to rate each of the words used in Study 1 from “extremely wrong” to “extremely right”. We find that these moral judgments can explain the framing effect in Study 1. In sum, our studies provide evidence that framing effects in an extreme Dictator game can be generated using morally loaded language.